Drug effects on the smooth muscle of the coronary system under physiological and pathological conditions - Szekeres László; Papp Gyula (Springer Netherlands Berlin, Heidelberg, 1994)
The preceding three sections described the structure, function and responsiveness to endogenous and exogenous substances of smooth muscles in different organ systems, predominantly under normal, physiological conditions. Section IV is devoted to the smooth muscle of the vascular system. The previous chapter dealt with the mode of action of antihypertensive agents protecting against hypertension, a pathological state representing an altered responsiveness of the peripheral vascular bed to drugs.
Keywords: Általános orvostudomány